Comparative study of rotahaler with metered dose inhaler in administering salbutamol in children with bronchial asthma - M. D., Balaji; Kamalammal, Rugmini (International Journal of Contemporary Pediatrics, 2016)
Background: It is estimated that around 300 million people suffer from asthma and the burden of this disease to families and patients is increasing worldwide. Reliver inhalations are the mode of management in acute exacerbation of asthma. Children of age 6-12 years can use both rotahaler and metered dose inhalers. This study compares the effectiveness of these two modalities in administration of salbutamol in acute exacerbation of asthma. Methods: A prospective study among 200 children with acute exacerbation of bronchial asthma in children in 6 to 12 years of age having mild to moderate persistent asthma. Acute exacerbation was defined as PEFR of <80% of the predicted value, children were randomly allotted to two groups and were administered salbutamol either by rotahaler or by metered dose inhaler. PEFR was measured before and after administration of 200 µg of salbutamol and reversibility of bronchoconstriction was statistically analyzed. Results: Mean increase in percentage of PEFR value after giving therapy was found to be 19.82 with SD -3.42, 21.9 with SD - 5.99, 20.61 with SD - 3.43, 21.31 with SD - 3.5 in rotahaler (Mild) group, rotahaler (Moderate) group, metered dose inhaler (Mild) group, Metered Dose Inhaler (Moderate) group respectively There was no statistically significant advantage of one modality over the other. Conclusions: Rapid relief of airway obstruction can be achieved in acute exacerbation of asthma by both the devices namely rotahaler and metered dose inhaler.